2008
DOI: 10.1111/j.1600-0722.2008.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post‐space treatment on retention of fiber posts in different root regions using two self‐etching systems

Abstract: The effect of post-space treatment on the retention of fiber posts in different root regions was evaluated using two self-etching systems. Post spaces were prepared in extracted premolars and then the root canals were subjected to one of the following post-space treatments: (i) water irrigation (control); (ii) etching with 35% phosphoric acid for 30 s; (iii) irrigation with 17% EDTA followed by 5.25% sodium hypochlorite (NaOCl); and (iv) ultrasonic agitation associated with 17% EDTA and 5.25% NaOCl irrigating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
72
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 28 publications
12
72
0
7
Order By: Relevance
“…Weakness could also be caused by the difficulty in accessing the apical region or restriction of the flow of adhesive resin cement (de Durâo Mauricio et al, 2007). However, some studies found no significant difference among root regions (Zhang et al, 2008;Babb et al, 2009). In our previous study, although we observed lower bond strength for PF in the apical region, the difference was not significant (Gu et al, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Weakness could also be caused by the difficulty in accessing the apical region or restriction of the flow of adhesive resin cement (de Durâo Mauricio et al, 2007). However, some studies found no significant difference among root regions (Zhang et al, 2008;Babb et al, 2009). In our previous study, although we observed lower bond strength for PF in the apical region, the difference was not significant (Gu et al, 2009).…”
mentioning
confidence: 99%
“…It is generally accepted that the efficacy of a dentin adhesive depends mostly on the removal of the smear layer and formation of a hybrid layer between the adhesive resin cement and the exposed collagen fibrils within the demineralized dentin (Pashley et al, 1993;Vichi et al, 2002). Adhesive resin cements developed over the past two decades have resulted in improved bond strength, at least when tested shortly after adhesion (Zhang et al, 2008;Bergoli et al, 2012), but the durability of bond strength is equivocal and remains an important issue (Kitasako et al, 2001;Toledano et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 They distribute the occlusal stress more uniformly along the root, leading to lower occurrence of root fractures. 4 However, the cementation of GFP is a sensitive technique and some variables may impair the bond between cement and dentin, such as the several materials used for endodontic treatment, [5][6][7] root canal morphological variations, 8,9 control of dentin moisture, formation of bubbles in the resin cement and difficult curing of the resin cement at the middle and apical root thirds. [5][6][7][8][9][10][11][12] Therefore, a successful treatment requires good bonding between…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2008) testaram, por meio do teste de "push out", a retenção de pinos intrarradiculares utilizando os adesivos Clearfil SE Bond e Clearfil DC Bond.…”
Section: Introductionunclassified